Early school leaving by children in out-of-home care: A comparative study of three Nordic countries. (October 2018) - Kääriälä, Antti; Berlin, Marie; Lausten, Mette; Hiilamo, Heikki; Ristikari, Tiina
Abstract: Previous studies have reported that children and adolescents who have been placed in out-of-home care for the protection of their safety and welfare face considerably high risks for early school leaving. Our study adds to the literature by comparing the association between children's exposure to placement in care and lack of secondary education (i.e. post-compulsory education after age 16) across three Nordic countries: Denmark, Finland, and Sweden. We use data from national registers for children born in 1987, following them until age 23. The datasets for Denmark (N = 55, 995, of whom 3056 are in care), Finland (N = 58, 855, of whom 1884 are in care), and Sweden (N = 100, 152, of whom 3209 are in care) cover the entire birth cohort. To estimate and compare country-specific risks, we calculate average marginal effects from binary logistic regression and adjust the effects for birth mother's socio-economic and health-related background. As expected, the results show that in each country, children placed in care had a significantly higher risk for early school leaving. After adjusting for maternal background, young adults who experienced out-of-home care were 24 to 39 percentage points more likely than their peers never in care to have not completed secondary education. Those placed in care for the first time at teenage were the most likely to have low attainment. In Finland and Sweden, children in care had a similar excess risk for early school leaving, whereas in Denmark the risk was higher. We discuss these results and recommend developing effective interventions to improve the educational attainment of children in care. The difference between Denmark and the other two requires further investigation. Highlights: We compare how many children in out-of-home care leave school early in Denmark, Finland, and Sweden. Those placed for the first time at teenage were the most likely to have low education in all countries. In those placed before teenage, attainment was less poor and associated with length of time in care. In Denmark, the risk for early school leaving was higher than in Finland and Sweden.